Upregulation of miR-101a Suppresses Chronic Renal Fibrosis by Regulating KDM3A via Blockade of the YAP-TGF-β-Smad Signaling Pathway - Hong Ding; Yanyan Xu; Nan Jiang (Elsevier, 2020)
Renal fibrosis denotes a common complication of diabetic nephropathy and is a predominant cause of end-stage renal disease. Despite the association between microRNAs (miRNAs or miRs) and renal fibrosis, miRNAs have been reported to play a vital role in the development of chronic renal fibrosis. Therefore, the aim of the present study was to investigate the possible function of miR-101a in chronic renal fibrosis. Initially, microarray-based gene expression profiling of renal fibrosis was employed to screen the differentially expressed genes. An in vivo mouse model of chronic renal fibrosis induced by a unilateral ureteral obstruction (UUO) and an in vitro cell model induced by aristolochic acid (AA) were constructed. miR-101a expression was examined using a fluorescence in situ hybridization (FISH) assay and quantitative reverse transcription polymerase chain reaction (qRT-PCR). Then, the interaction between miR-101a and KDM3A was identified using an online website combined with a dual-luciferase reporter assay. Finally, gain- and loss-of-function experiments were conducted to elucidate the effect of miR-101a on the expression of Col1a1, fibronectin, α-smooth muscle actin (α-SMA), and YAP-TGF-β (transforming growth factor β)-Smad signaling pathway-related genes, as well as the degree of renal fibrosis. miR-101a was poorly expressed while KDM3A was robustly induced in chronic renal fibrosis tissues and cells. In addition, miR-101a could target and downregulate KDM3A expression, which led to elevated TGIF1, inhibited expression of Collagen I (Col1a1), fibronectin, α-SMA, YAP1, and TGF-β2 along with the extent of Smad2/3 phosphorylation, as well as delayed renal fibrosis degree. Besides, overexpressed YAP/TGF-β2 or inhibited TGIF1 partially restored the inhibitory effect of miR-101a on chronic renal fibrosis. Taken together, miR-101a could potentially slow down chronic renal fibrosis by the inactivation of the YAP-TGF-β-Smad signaling pathway via KDM3A, highlighting the potential of miR-101a as a therapeutic target for chronic renal fibrosis treatment. Keywords: chronic renal fibrosis, microRNA-101a, KDM3A, YAP-TGF-β-Smad signaling pathway, enhancer, TGIF1